Quality of Life in Late-Treated Patients With Disorders of Sex Development: Insights for Patient-Centered Care - Ediati, Annastasia; Verrips, Gijsbert H. W.; Juniarto, Achmad Zulfa; Faradz, Sultana M. H.; Drop, Stenvert L. S.; Dessens, Arianne B. (Frontiers in Pediatrics, 2019)
Background: Patients with a disorder of sex development (DSD) are born with atypical genitals or may develop atypical genitals and atypical body appearance, if left untreated. Health related quality of life (HRQoL) was assessed in Indonesian patients to whom diagnostic procedures and medical intervention had been delayed. Method: Comparison of 118 patients born with DSD, aged 6–41 years (60 children, 24 adolescents, and 34 adults) and 118 healthy control subjects matched for gender, age, and residential setting. HRQoL was measured using a translation of the TACQOL/TAAQOL. Results: According to parental and children's report, children with DSD reported more problems in social functioning and had less positive moods. Girls, in particular, reported problems in cognitive functioning. Adult patients reported more depressive moods, especially women, who reported more anger. No differences were found between in the adolescent groups. Conclusion: The data suggest that Indonesian children with DSD experienced more problems in social contact than non-affected Indonesian children, whereas Indonesian adults with DSD suffered from negative emotions more often than non-affected Indonesians. These findings on HRQoL are in line with findings on emotional functioning.